2013
DOI: 10.1007/s10815-013-0037-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of blastocysts derived from fair to poor quality cleavage stage embryos can produce high pregnancy rates after warming

Abstract: Supernumerary average quality day 3 embryos should be given a second chance to be selected for cryopreservation. If blastocysts are obtained and survive vitrification, there is a good chance of implantation thus reducing embryo waste.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 43 publications
4
21
2
Order By: Relevance
“…We have previously demonstrated that embryos that do not fulfill the current morphological or morphokinetic criteria still have the potential to develop to a blastocyst and lead to the birth of a healthy baby [48]. Such observations are supported by other studies showing that even vitrification of blastocysts derived from fair-to poor-quality cleavage-stage embryos can produce high pregnancy rates after warming [49,50].…”
Section: Discussionmentioning
confidence: 55%
“…We have previously demonstrated that embryos that do not fulfill the current morphological or morphokinetic criteria still have the potential to develop to a blastocyst and lead to the birth of a healthy baby [48]. Such observations are supported by other studies showing that even vitrification of blastocysts derived from fair-to poor-quality cleavage-stage embryos can produce high pregnancy rates after warming [49,50].…”
Section: Discussionmentioning
confidence: 55%
“…The embryos were evaluated and fixed immediately, or cultured another 24 hr (Days‐4 and ‐6 embryos) or 48 hr (Day‐7 embryos) before evaluation and fixation. A few of the poor‐quality embryos that became available at Day 3 developed into good‐quality embryos, which was reported before (Ren et al, ; Shaw‐Jackson et al, ); however, the majority remained of poor‐quality, so those embryos were included in the poor‐quality group.…”
Section: Methodsmentioning
confidence: 59%
“…Although previous studies have already reported a potential for PQE to develop to the blastocyst stage, with some even capable of implantation (Alikani et al, 2000;Balaban et al, 2001;Shaw-Jackson et al, 2013;Stone et al, 2005), these embryos are usually destroyed or destined for research purposes. A possible explanation may be the poor morphology of these embryos on day 3, which is not compatible with freezing programmes.…”
Section: Discussionmentioning
confidence: 99%